2022
DOI: 10.1021/acsmacrolett.2c00425
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Organocatalysts for Stereoselective Ring-Opening Polymerization of Racemic Lactide at Room Temperature

Abstract: Although significant advances have been achieved, highly stereocontrolled polymerization using organocatalysts is still a great challenge, such as ring-opening polymerization of racemic lactide (rac-LA) for the synthesis of stereoregular polylactide (PLA). In this context, a series of binary organocatalysts consisting of different phosphazenes (CTPB, C3N3-Me-P3, C3N3-Py-P3, t-BuP2, and t-BuP4) and achiral ureas (U1–U6) were applied for the stereocontrolled ROP of rac-LA under mild conditions. It is remarkable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…First, achiral ureas with electron‐withdrawing substituents on the benzene rings ( U‐1 and U‐2 ) were combined with m ‐PDPB to evaluate the polymerization behavior of rac ‐LA (Table 1, runs 3–5). It has been reported that the addition of excess ureas could improve the solubility of the initiator/urea anion mixtures and a ratio of [urea] 0 /[base] 0 = 3/1 was generally adopted in the reported urea/base catalytic systems to ensure good solubility 40,51,52 . Therefore, a molar ratio of 1/3/1 between the base, the urea and the initiator was employed for the preliminary ROP experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, achiral ureas with electron‐withdrawing substituents on the benzene rings ( U‐1 and U‐2 ) were combined with m ‐PDPB to evaluate the polymerization behavior of rac ‐LA (Table 1, runs 3–5). It has been reported that the addition of excess ureas could improve the solubility of the initiator/urea anion mixtures and a ratio of [urea] 0 /[base] 0 = 3/1 was generally adopted in the reported urea/base catalytic systems to ensure good solubility 40,51,52 . Therefore, a molar ratio of 1/3/1 between the base, the urea and the initiator was employed for the preliminary ROP experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Newly designed chiral bifunctional squaramides could mediate the stereoselective ROP of rac ‐LA to prepare PLAs with P m up to 0.88 at 25°C 37 . Very recently, we found that phosphazene/urea with compatible basicity/acidity showed both high activity and great stereoselectivity ( P m = 0.92) toward the ROP of rac ‐LA at room temperature 40 . Although these progresses have been made, organocatalyzed stereoselective ROP of rac ‐LA under mild reaction conditions remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…, use of non-metallic catalysts for creation of C–C or C–X bonds with high stereoselectivity, has truly emerged in the early 2000s. These developments, which were crowned in 2021 with the award of the Nobel Prize in Chemistry to McMillan and List, have led to organic catalysts constituting today the third pillar of catalysis, besides enzymes and metallic catalysts. In contrast, adaptation of this concept in polymer synthesis, i.e. , stereoselective polymerization employing chiral organic catalysts, is more recent and remains underexplored. In a more general way, organic catalysts, whether they are chiral or not, that can provide high stereoselectivity and high catalytic activity, in addition to operating under mild conditions, e.g., at room temperature or above, are rare. Yet, the use of small organic molecules for organic catalysis of polymerization is now part of the methodological toolbox in macromolecular synthesis. Depending on the structure of the organic catalyst, different mechanisms can operate, and this diversity of mechanistic pathways allows for improved polymerization rates, tuning of the selectivity, and rational design of a variety of polymer architectures. Organic catalysis of polymerization can offer other advantages over metal-catalyzed reactions, such as a reduced toxicity and cost, easier catalyst synthesis and storage, tolerance to functional groups, and operation at elevated temperatures and in a variety of solvents. Recent years have witnessed new achievements at the crossroads between organocatalysis and macromolecular science, for instance, through the use of organic catalysts for photopolymerization or for controlled radical polymerization, for chemical recycling and upcycling of synthetic polymers, or for designing covalent adaptative networks …”
Section: Introductionmentioning
confidence: 99%
“…, made from the two LA monomer units of opposite configurations, may be obtained at lower cost by stereocontrolled ROP of rac -LA, leading to PLA-based materials of enhanced properties. , Since the 1990s, and until recent years, the stereochemical control of the ROP of rac -LA has been intensively investigated using metal catalysts operating by a coordination–insertion mechanism. , As mentioned, however, specific design and/or storage of organometallic complexes can be demanding, in addition to their often-proven cytotoxicity. In that respect, organic catalysts have appeared as promising alternatives for the stereoselective ROP of rac -LA. …”
Section: Introductionmentioning
confidence: 99%
“…Second, the stabilization of the carbamate anion propagating intermediate by tripodal tri-thiourea (TTU) via anion-binding interaction enables chain elongation to proceed in a synergistic decarboxylation fashion and avoids the formation of undesired highly basic −NH – propagating species, reducing the basicity and nucleophilicity of the anionic propagating species, thereby minimizing extensive side reactions and the “activated monomer” pathway. Third, the activation of tri-thiourea upon the NCA monomer through classical H-bonding combined with propagation in a synergistic decarboxylation fashion can prevent inherent helix-induced self-acceleration in less-polar solvents, resulting in chain initiation rate at least comparable to that of propagation.…”
Section: Introductionmentioning
confidence: 99%